Dual Field Calibration of Capacitance and Neutron Soil Water Sensors in a Shrinking–Swelling Clay Soil - Fares, A.; Buss, P.; Dalton, M.; El‐Kadi, A. I.; Parsons, L. R. (Vadose zone journal, 2004)
Multisensor capacitance sensors (MCS) are now popular alternatives to neutron scattering (NS) soil water–monitoring devices. The objectives of this study were to (i) quantify the effect of clay shrinkage–swelling on the soil bulk density; (ii) determine field calibration equations for an MCS and an NS device; and (iii) compare the performance of the MCS with a NS meter under field conditions. The calibration was conducted in a duplex soil with sandy clay loam overlying clay in South Australia. Six access tubes were installed in a 6 by 8 m grid. Three moisture treatments were replicated twice for every moisture level. The bulk density of the top 20 cm increased with increasing water content; this increase was more pronounced in the upper 10‐cm horizon, which could be attributed to soil compaction. However, a negative correlation was obtained between bulk density and water content in the 30‐ to 100‐cm depth layers reflecting the shrinking and swelling properties of the fine‐textured subsoil. Results also show highly significant effects of sampling depth and moisture level on NS and MCS readings. Compared with linear calibration, a three‐parameter model improved NS calibration and/or minimized the root mean square errors for 6 out of the 10 sampling depths. Except for the 10‐cm sampling depth, individual calibration for each 10‐cm soil layer improved the accuracy of the MCS as compared with the use of single calibration equation for the entire profile. Site‐specific calibration improved the accuracy of both the NS and MCS soil water–monitoring devices.